Role of international registries in enhancing the care of familial hypercholesterolaemia - Hammond, E.; Watts, G.; Rubinstein, Y.; Farid, W.; Livingston, M.; Knowles, J.; Lochmuller, H.; Bellgard, M.; Dawkins, Hugh (Wiley-Blackwell Publishing Asia, 2013)
Familial hypercholesterolaemia (FH) is a relatively common genetic disorder associated with high risk of coronary heart disease that is preventable by early diagnosis and treatment. In a previous article, we reviewed the evidence for clinical management, models of care and health economic evaluations. The present commentary emphasises that collective action is needed to strengthen our approaches to evidence-based care, including better diagnosis and access to effective therapies. We detail how contemporary innovations in inter-operable, web-based, open-source and secure registries can provide the supporting infrastructure to: (i) address a current gap in the flow of data for measuring the quality of healthcare; (ii) support basic research through provision of high-quality, de-identified aggregate data; (iii) enable equitable access to clinical trials; and (iv) support efforts to disseminate evidence for best practice and information for care services. We describe how these aspects of enabling infrastructure will be incorporated into the development of a National FH Registry for Australasia, and proffer that a coordinated response to FH would be enhanced through a global network of inter-operable registries.